Robert Bruce : and the community of the realm of Scotland - Barrow, G. W. S. (Berkeley : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1965.
A kingdom in perplexity -- Bruce of Annandale -- Bruce versus Balliol -- A lamb among wolves -- Two kinds of war -- Experiments in guardianship -- The king over the water -- Defeat -- Revolution -- A king in search of his throne -- The turn of the tide -- Bannockburn -- War and peace -- Good King Robert -- In search of Robert Bruce.
Description based upon print version of record.
Includes bibliographical references and index.
JSTOR
Keywords: Robert -- I, -- King of Scots, -- 1274-1329.; Robert -- I, -- King of Scots, -- 1274-1329; Scotland -- History -- War of Independence, 1285-1371.; Écosse -- Histoire -- 1285-1371 (Guerre d'indépendance); HISTORY / Europe / Great Britain / Scotland; Scotland; 1285-1371; History